Measurements of flow patterns around a wide wing-wall abutment in floodplain - Yeh, Yi Min (2018)
Scour around bridge support structures such as piers and abutments, is a widespread problem. As removal of ground materials results in lowering of stream bed, this will make the bridge more susceptible to structure failure. Bridge failure is a great concern which could cause significant transport disruption, economic loss, and in the worst case, the loss of lives. In order to better estimate the characteristics of scour formed for corrective actions, it is important to be able to predict the flow in scouring process around piers and abutments.